Factors influencing the spatial distribution and individual variation in urinary fluoride levels in Tibet, China. (June 2023) - Zhang, Ru; Yang, Yi; Deji, Yangzong; Li, Hairong; Li, Yonghua; Nima, Cangjue; Zhao, Shengcheng; Gong, Hongqiang
Abstract: Nowadays, fluorosis is the most prevalent endemic disease in Tibet and one of the most concerned public health problems in China; urinary fluoride is a common diagnostic indicator of endemic fluorosis. However, the spatial distribution and influencing factors of urinary fluoride content in Tibet remain unclear. This study aims to bridge this gap by geographically weighted regression (GWR), analyses of variance (ANOVAs), Geodetector, and stepwise multiple linear regression (MLR). To achieve this goal, this study first investigated fluoride levels in the fasting urine among 637 Tibetan residents from 73 counties in Tibet, the urinary fluoride level was chosen as an indicator of fluorosis, which can reflect the health impairment. Then we identified the potential factors that could influence the spatial distribution and individual variation of urinary fluoride levels from physical environmental and socioeconomic perspective, respectively. The results showed that urinary fluoride levels in Tibet were slightly exceeding the average value for adult urinary fluoride in China, and that residents with high urinary fluoride were mainly found in the west and east; those with low urinary fluoride were mainly found in the central-southern regions. And the urinary fluoride levels had a significantly positive correlation with water fluoride and a significantly negative correlation with average annual temperature. Urinary fluoride levels increased until age 60 and followed an inverted "U"-shaped trajectory according to annual household income (80, 000 renminbi (RMB) was the inflection point); pastoralists had greater exposure to fluoride than farmers. Furthermore, the Geodetector and MLR showed that the urinary fluoride level was influenced by both physical environmental and socioeconomic factors. The socioeconomic factors such as age, annual household income and occupation had a greater impact than the physical environment on urinary fluoride concentration. These findings can provide scientific basis for preventing and controlling endemic fluorosis in the Tibetan Plateau and adjacent areas. Graphical abstract: Image 1 Highlights: First human fluoride biomonitoring study conducted throughout Tibet, China. Levels and distribution pattern of urinary F in Tibetan residents were obtained. Women and pastoralists were more sensitive to F exposure than men and farmers. Socioeconomic factors have greater impact on urinary F than physical environment.